(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper explores the application of complex intuitionistic fuzzy sets to the study of quasi-associative ideals in BCI-algebras. We introduce a new concept—complex intuitionistic fuzzy quasi-associative ideals in BCI-algebras—and analyze their fundamental properties. The relationships between complex intuitionistic fuzzy ideals and complex intuitionistic fuzzy quasi-associative ideals are investigated in detail. Furthermore, we present key characterizations of these quasi-associative ideals, providing deeper insights into their structure and role within BCI-algebraic systems. Finally, we prove that every complex intuitionistic fuzzy b-ideal is a complex intuitionistic fuzzy quasi-associative ideal in BCI-algebras.